LINGUISTIC AND SEMIOTIC ANALYSIS OF THE PHRASEOLOGICAL FIELD OF «CLOTHES" (IN THE EXAMPLE OF ENGLISH, RUSSIAN, AND UZBEK LANGUAGES) - Arslonzoda Aziza Rahmatovna (Journals Park Publishing, 2022)
In modern linguistics, the phraseological level is understood in a narrow and wide range, and the terms representing stable word combinations have different and controversial definitions. Relations between language and culture from the implicit meaning of reality in the semantics and structure of language units manifests itself in various forms up to the explicit appearance. The following article is devoted to the linguistic and semiotic analysis of the phraseological field of " clothes" in the example of the English, Russian and Uzbek languages.
Keywords: semiotic analysis, phraseology, culture, hierarchy, phraseological unit